(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and investigate some factors related to anxiety disorders in cirrhotic patients at the Gastroenterology Department - Viet Tiep Friendship Hospital in 2025. Method: Cross-sectional descriptive study, convenient sampling on 144 cirrhotic patients at the Gastroenterology Department - Viet Tiep Friendship Hospital from January to March 2025. Results: The prevalence of anxiety disorders was 43,1%; of which patients with mild anxiety disorders accounted for 24,3%. Analysis of some related factors showed: There was a statistically significant correlation between anxiety status and disease stage and frequency of hospitalization in the past year. There was no correlation between anxiety status and age group, gender, cause of disease, or caregiver. Conclusion: 43,1% of cirrhotic patients had anxiety disorders, of which mild anxiety disorders accounted for 24,3%. There is a correlation between anxiety levels and disease progression and the frequency of hospitalizations in the past year. Therefore, to improve anxiety levels in patients, nurses need to clearly explain the disease, provide emotional support, especially for patients in the decompensated cirrhosis stage.